Development of Problem-Based Learning Video Learning Media on Human Digestive System Material on Critical Thinking Skills - Larasati, Riwanda Citha; Zurweni, Zurweni; Hariyadi , Bambang (STAI Miftahul Ula Nganjuk, 2024)
This developmental research aims to evaluate the feasibility and effectiveness of video-based learning media on the human digestive system material. The background of this study is based on the observation that students remain passive when solving problems, show low enthusiasm during learning processes, have underdeveloped critical thinking skills, experience difficulty in understanding the digestive system material, and the lack of existing video-based learning media for this topic. This developmental research follows the Lee & Owens development model. Data collection techniques include questionnaires and tests, with data analysis consisting of both qualitative and quantitative approaches. Based on validation results from media and design experts as well as content experts, the developed video-based learning media was deemed feasible and ready for testing. Teacher evaluations classified the media as highly feasible, while student responses in the individual trial phase yielded a very good category with a percentage of 92.77%. Similarly, in the small group trial, the student response was also very good, with a percentage of 93.14%. The analysis of pretest-posttest results of students' critical thinking skills using the n-gain test showed a score of 0.60, which falls into the moderate category. It can be concluded that video-based learning media, incorporating problem-based learning, is an effective educational tool to enhance students' critical thinking skills in the human digestive system material.